Determinants of behavioral intention of fraudulent financial reporting: Using the theory of reasoned action - Mohamed Zawawi, Siti Noor Hayati; Md. Idris, Kamil; Abdul Rahman, Rashidah (Malaysian Accountancy Research and Education Foundation, 2011)
The main aim of this study was to identify factors that determined the behavioral intention of fraudulent financial reporting.Since fraudulent financial reporting involves unacceptable human behavior, the social psychology theory of reasoned action was used to identify the behavioral factors that could explain this behavior.Using the structural equation modeling, the results indicate that the attitude toward behavior and the subjective norm significantly influenced the behavioral intention of fraudulent financial reporting.However, the subjective norm was a more important predictor than the attitude toward behavior.Overall, the results show that the theory of reasoned action was successful in explaining the fraudulent financial reporting behavior.